2018
DOI: 10.1111/ijac.12856
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of SiC from acid‐leached coal gangue by carbothermal reduction

Abstract: For the comprehensive utilization of coal gangue, acid‐leached coal gangue was used as silicon source and part of carbon source, low ash anthracite and degreasing cotton were added respectively as supplementary carbon source, SiC and SiC fiber were prepared by carbothermal reduction method accordingly. The results show that the main components in leached coal gangue are amorphous SiO2 and carbon, which are suitable for the synthesis of SiC as raw materials. The synthesis temperature and holding time have impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…iron tailings, porous materials, reaction sintering, reduction, silicon carbide, thermal conductivity particles, rendering them to be suitable for sintering. [14][15][16] It is shown that combining the carbothermal reduction with the nitridation process can also produce high thermal conductivity AlN ceramics. 17 and high porosity porous silicon nitride ceramics for filters and catalyst carriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…iron tailings, porous materials, reaction sintering, reduction, silicon carbide, thermal conductivity particles, rendering them to be suitable for sintering. [14][15][16] It is shown that combining the carbothermal reduction with the nitridation process can also produce high thermal conductivity AlN ceramics. 17 and high porosity porous silicon nitride ceramics for filters and catalyst carriers.…”
Section: Introductionmentioning
confidence: 99%
“…The carbothermal reduction is an attractive method to prepare carbide ceramics with high performance due to the extensive raw material sources, low process cost and simple operation. The products possess high purity and small‐sized particles, rendering them to be suitable for sintering 14‐16 . It is shown that combining the carbothermal reduction with the nitridation process can also produce high thermal conductivity AlN ceramics 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The Omsk CFA mainly contains 20-35 wt % alumina, 50-65 wt % silica, 5-15 wt % magnetite, and up to 6 wt % unburned carbon [1,2]. Previous research was aimed mainly at studying methods for producing alumina [3][4][5][6], ceramics [7][8][9][10], coagulants [11,12], and the extraction of the rare-earth elements [13][14][15][16][17]. Our previous research was about the leaching of alumosilicates with hydrochloric acid…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, a uniform ceramic slurry having a high solid content and a low viscosity must be prepared that is a prerequisite for the implementation of this process. [1][2][3] However, a uniform ceramic slurry having a high solid content and a low viscosity must be prepared that is a prerequisite for the implementation of this process.…”
Section: Introductionmentioning
confidence: 99%
“…The colloidal process is one of the effective methods to prepare high reliability, high density, and complex silicon carbide (SiC) ceramic components. [1][2][3] However, a uniform ceramic slurry having a high solid content and a low viscosity must be prepared that is a prerequisite for the implementation of this process. 4,5 It is well known that high solid content and low viscosity are contradictory.…”
Section: Introductionmentioning
confidence: 99%